Forging Loyalty in Non-Metropolitan Hospitality Through Service Quality and Satisfaction - Echo Perdana Kusumah; Iza Guspian (Politeknik Sahid, 2026)
This study examines how service quality dimensions—tangibles, reliability, responsiveness, assurance, and empathy—shape customer loyalty through the mediating role of satisfaction in non-metropolitan hospitality settings. Focusing on four-star hotels in Pangkalpinang, Indonesia, the research addresses the limited empirical evidence from emerging tourism destinations outside metropolitan areas. A quantitative cross-sectional approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Data were collected from 340 hotel guests through structured questionnaires, employing non-probability convenience sampling in leisure and dining areas. Reliability and validity tests were conducted prior to structural analysis. Findings contribute to hospitality theory by confirming the full mediating effect of satisfaction between service quality and loyalty in a non-metropolitan context. For practitioners, the results highlight the strategic importance of enhancing empathy and tangibles to create lasting guest relationships, offering a competitive edge for hotels in emerging tourism markets.